2008
DOI: 10.1002/cncr.23661
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing docetaxel chemotherapy in patients with cancer of the gastric and gastroesophageal junction

Abstract: Advanced gastroesophageal cancer patients are often treated with systemic combination chemotherapy. The V-325 study demonstrated that adding docetaxel (D) to a frequently used regimen of cisplatin and 5-fluorouracil (CF) provided benefits with regard to overall survival, response rate, time-to-disease progression, clinical benefit, and health-related quality of life. Although the DCF regimen provides these advantages, it is accompanied by an increase in toxicity compared with the doublet regimen. The toxici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 54 publications
2
42
0
Order By: Relevance
“…On the other hand, response rate achieved in 71.4% (5/7). In addition, Ajani et al reported a excellent response rate (55.7%) of systemic DCF therapy combined with docetaxel 75 mg/m 2 on day 1 for 3 weeks, CDDP 75 mg/m 2 day 1 for 3 weeks, and 5FU 750 mg/m 2 day 1-5 for 3 weeks [12]. The dose of the docetaxel and CDDP per 1 course of DCF therapy is similar to those of the present study.…”
Section: Journal Of Surgical Oncologysupporting
confidence: 89%
See 1 more Smart Citation
“…On the other hand, response rate achieved in 71.4% (5/7). In addition, Ajani et al reported a excellent response rate (55.7%) of systemic DCF therapy combined with docetaxel 75 mg/m 2 on day 1 for 3 weeks, CDDP 75 mg/m 2 day 1 for 3 weeks, and 5FU 750 mg/m 2 day 1-5 for 3 weeks [12]. The dose of the docetaxel and CDDP per 1 course of DCF therapy is similar to those of the present study.…”
Section: Journal Of Surgical Oncologysupporting
confidence: 89%
“…Recently, Ajani reported that DCF therapy (a combination chemotherapy using docetaxel, CDDP and 5FU) showed a significant better survival than CF (CDDP þ 5FU) therapy [12]. However, there has been no report to study the efficacy of systemic chemotherapy on patients with PC from gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The disease stabilization rates in both trials are similar (66.7% vs. 67%). Our results and other reports with the DCF regimen suggest that along with their cytotoxic effects on gastric cancer the drugs in this combination might change the behavior of the disease, possibly by inhibition of angiogenesis, to improve the survival (21,22).…”
Section: Discussionsupporting
confidence: 68%
“…Cisplatin plus 5-fluorouracil (CF) and epirubicin plus CF (ECF) regimens have been investigated widely in clinical studies and were, until recently, presented as the reference regimens [2][3][4][5][6][7][8][9][10][11][12]. The activity of docetaxel in gastric cancer was first demonstrated in phase II single-agent studies: reported overall response rates (ORRs) were 16-24 % in the first-line setting [13][14][15][16][17]. The combination of docetaxel and cisplatin (DC) as a first-line chemotherapy was revealed to have a modest anti-tumor effect and manageable toxicity for the palliative treatment of AGC [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Despite a higher incidence of some toxicities as a result of the addition of docetaxel to CF, the quality-of-life results of the V325 trial consistently favored DCF over CF, supporting the benefit of DCF [25]. Following the results of the V325 trial, the DCF has become a new reference regimen in AGC [3,13]. However, the toxicity profile of the DCF regimen has contributed to the limitations of using this combination.…”
Section: Introductionmentioning
confidence: 99%